2018 IEEE Energy Conversion Congress and Exposition (ECCE) 2018
DOI: 10.1109/ecce.2018.8557562
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Efficiency and Cost Limits of Fractional hp Axial Flux PM Machine Designs

Abstract: Optimizing the design of electric machines is a vital step in ensuring the economical use of active materials. The three-dimensional flux paths in axial flux PM (AFPM) machines necessitate the use of computationally expensive 3D electromagnetic analysis. Furthermore, a large number of design evaluations is required to find the optimum, causing the total computation time to be excessively long. In view of this, a two-level surrogate assisted algorithm capable of handling such expensive optimization problems is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This paper is an expanded follow-up to a previous conference paper by the same authors [16]. Together the current and the previous conference paper provide substantial contributions to the subject matter by: systematically investigating the optimal design and pole count selection of a surface mounted AFPM machine; employing an algorithm capable of solving optimization problems with 3D FEA design evaluations and a very wide search space; and proposing a method for interpreting the Pareto front and selecting the optimal design in a multi-objective problem.…”
Section: Introductionmentioning
confidence: 85%
“…This paper is an expanded follow-up to a previous conference paper by the same authors [16]. Together the current and the previous conference paper provide substantial contributions to the subject matter by: systematically investigating the optimal design and pole count selection of a surface mounted AFPM machine; employing an algorithm capable of solving optimization problems with 3D FEA design evaluations and a very wide search space; and proposing a method for interpreting the Pareto front and selecting the optimal design in a multi-objective problem.…”
Section: Introductionmentioning
confidence: 85%
“…1. An algorithm based on surrogate models and differential evolution, employing 3D models and elaborated in [8], [9], is utilized for the optimization study. It is demonstrated that the combined use of this surrogate assisted optimization technique, together with the proposed definition of the search space results in substantial savings in computation time.…”
Section: Introductionmentioning
confidence: 99%